Does Service-Based Learning Strengthen Students’ Core Skills? - Firman, Firman; Prianto, Agus; Munawaroh, Munawaroh; Timan, Agus (International Journal of Learning, Teaching and Educational Research, 2024)
The Ministry of Education, Culture, Research and Technology of the Republic of Indonesia launched the Learning Freedom, Independent Campus policy at the beginning of 2020. The aim of this new strategy is to give universities the chance to adapt learning, so that higher education learning activities are more adaptable and reinforce students’ core skills. Various universities are developing service-based learning, which is implemented through three learning models, namely, humanitarian projects (HP), thematic work lecture (TWL), and teaching assistance (TA). This study aimed to describe students’ involvement in service-based learning and its impact on students’ core skills. The population of this study were students from major state universities in East Java who had participated in HP, TWL, and TA. The sample was determined using systematic random sampling. Data analysis was carried out using a descriptive approach and multivariate analysis. This study found that students were highly involved in HP, TWL, and TA. Overall, the service-based learning model strengthens students’ core skills. Sequentially, HP, TWL, and TA are service-based learning models that effectively strengthen students’ lifelong learning, communication, and problem-solving skills. Meanwhile, TWL is very effective in strengthening students’ teamwork skills. Further research is recommended to elaborate and validate specific skills as part of the core skills components. This research does not discuss in detail students’ involvement in service-based learning, and their core skills as influenced by gender, academic ability, socioeconomic background, and departmental differences. This was a limitation in this research, so further research is needed. https://doi.org/10.26803/ijlter.23.6.27